Highly fluidic liquid at homointerface generates grain-boundary dislocation arrays for high-performance bulk thermoelectrics. (15th October 2018) - Mun, Hyeona; Lee, Kyu Hyoung; Yoo, Seung Jo; Kim, Hyun-Sik; Jeong, Jiwon; Oh, Sang Ho; Snyder, G. Jeffrey; Lee, Young Hee; Kim, Young-Min; Kim, Sung Wng
Abstract: Dislocation arrays embedded in low-angle grain-boundaries have emerged as an effective structural defect for a dramatic improvement of thermoelectric performance by reducing thermal conductivity [1]. A transient liquid-flow assisted compacting process has been employed for p-type Bi0.5 Sb1.5 Te3 material to generate the dislocation arrays at grain-boundaries. The details of underlying formation mechanism are crucial for the feasibility of the process on other state-of-the-art thermoelectric materials but have not been well understood. Here, we report the direct observation of dislocation formation process at grain-boundaries of Sb2 Te3 system as a proof-of-concept material. We found that the formation of homointerface between Te-terminated Sb2 Te3 matrix phase and Te liquid atomic-layer of secondary phase is a prerequisite factor to achieve the low-energy liquid-solid homointerface at compacting elevated temperature. We further demonstrate from the successful observations of atomic structure in the intermediate state of the compacted pellet that the high self-diffusion rate of Te atoms at the liquid-solid homointerface facilitates an effective grain rearrangement, generating low-energy grain-boundaries embedded with dense dislocation arrays. These results pave the way to improve thermoelectric performance of various materials where dislocation arrays are generated by transient liquid-flow assisted compacting process using precursors with an interface constructed with the same types of atoms. Graphical abstract: Image 1